WAYS TO REDUCE THE RISKS OF INFECTION WHILE TRAINING FOR WORK WITH MICROORGANISMS OF THE I–II GROUPS OF PATHOGENICITY (HAZARD) - E. V. Rastuntseva; L. A. Tikhomirova; E. V. Sazanova (Проблемы особо опасных инфекций, 2017)
Minimization of risks of infection when training the specialists to work with microorganisms – agents of particularly dangerous infectious diseases – is one of the key objectives for staff members of the Department for specialists training and curricula development at the FGHI RusRAPI “Microbe”. The paper discusses the ways to reduce the risks of infection with agents of particularly dangerous infectious diseases among the attendee and the tutors of qualification courses while studying how to work with this group of microorganisms. Outlined are priority areas: usage of attenuated, avirulent strains of the agents, as well as recombinant strains of nonpathogenic bacteria; exploitation of the state-of-the-art technical equipment; insure the skills of safe PBA handling and professionally significant traits of character in the process of realization of currently existing academic programs. Identified has been the optimum approach to the assessment of reliability and safety of professional activities among the personnel working with PBA of the I–II groups of hazard. Developed has been the algorithm for competence level evaluation in the specialists who are allowed to work with PBA of the I–II groups of hazard; job profile diagrams have been charted. Designed methods of expert evaluation of professionally significant skills and traits of the staff provide for personnel identification using a range of psychological tests and play an important role in vocational selection and orientation, both during the job placement and advanced training of the staff, as well as in the reduction of risks associated with the factor of human error.